تصميم كراسات التدريبات لمهارة الكلام بمدرسة خير الدين المتوسطة الإسلامية بكونداع لاجي مالانج - Khusnul Khotimah (LISANIYAT, 2010)
Drill is a collection of various problems that demands students to solve the problem. Drill is important to help students understanding more about the subjects they have studied. Even though it is very necessary in improving speaking skill and accustoming the students to spell letters and words correctly and to speak Arabic well, the drill is overlooked in teaching language at MTs Khairuddin. Based on the background above, the researcher compiled special Worksheet (LKS) containing exercises for speaking skill. The research questions on the LKS are as follows:  1) how the exercises compiled improve the speaking skill?, and 2) how far is LKS effective in improving the speaking skill of MTs Khairuddin students?The method used in this research is RD method of seven steps: 1) first study, 2) planning development, 3) product/design development, 4) expert judgment, 5) revision, 6) experiment, and 7) revision and completion. When all the steps are concluded, it will be tested in class VII students of MTs Khairuddin, with random samples of 20 students. Using pre-test and post-test, the research uses two samples, that of control class and that of experiment class.The result is as follows: the post-test of control group 163 and experiment group value 223. After being calculated by t test formulation using SPSS 12 program, it is revealed that tcalculation = 6 more than ttable = 1.734, with significance level of 0.00 lower than α = 0.05. Based on the data, HO is rejected. It means that there is significant difference between control and experiment group. The result shows us that LKS is effective in improving speaking skill of class VII students of MTs Khairuddin Gondanglegi.Keywords: Drill, LKS design